Relationship Between Risk Tasking And Sharia Bank Performance: Evidence From Islamic Bank In Asia - Mega Metalia (Universitas Muhammadiyah Malang, 2023)
Purpose: This study aims to examine the relationship between human capital efficiency (HCE), structural capital efficiency (SCE), capital employed efficiency (CEE), risk taking, sharia governance, and the performance of Islamic banks based on the maqasid shariah index (MSI), as well as the moderating effect of governance sharia on the relationship between risk taking and performance. Methodology/approach: This study uses secondary data from the Bankscope database for 2014 - 2018, The test is carried out using a dynamic panel regression two-step generalized method of moments (GMM). The total population is all non - window banking Islamic banks from various countries, namely 96 banks. The sample that passed the selection based on the criteria were 75 banks. Findings: The results showed that there was a significant positive relationship between HCE, SCE, and CEE with the performance of Islamic banks. Risk taking has a significant negative effect on performance. The results of this study further indicate that governance positively moderates the relationship between risk taking and performance. Practical implications: The results of the study can provide an analysis of the specific impact of the effect of the size category of Islamic banks on the performance of Islamic banks. Originality/value: One of the novelty of this study is the analytical model links the influence of intellectual capital proxied by HCE, SCE, and CEE, risk taking, sharia governance with sharia bank performance.